Reconfigurable group delay with tunable topological edge state based on phase transitions material Ge2Sb2Te5 in dual-band - Yao Lu; Qiaohong Yao; Mengdong He; Jiao Xu; Yuxiang Peng (Results in Physics)
We investigate reconfigurable reflected group delay in dual-band of the photonic crystal heterostructure containing phase transitions material Ge2Sb2Te5 and graphene in mid-infrared region. The giant phase change of reflected beam derives from the topological edge state excited at the boundary surface of photonic crystal. Meanwhile, the tunable topological edge states can be satisfied by controlling the reversible switching between the crystalline and amorphous states of the Ge2Sb2Te5, which provides a flexible way to achieve configurable group delay in dual-band. Besides, the reflected group delay can be dynamically controlled by controlling Fermi energy, relaxation time of graphene and the incident angle. The reconfigurable reflected group delay in dual-band presented in this paper has the potential to be used in high-efficiency memory for optical pulses and optical delay lines.